The Influence Of Brand Image, Service Quality, And Price On Purchase Decision At Nail Studio In Manado - Kareninan Anatasya Liliana Owu; Marjam Mangantar; Lawren Julio Rumokoy (Nusantara Journal of Multidisciplinary Science, 2024)
Nowadays nail beauty is increasingly varied, not only caring for nails but nail beauty has also led to decorating nails or improving nail conditions and can even cover imperfections in women's nails. This research was conducted to test empirically whether brand image, price, and service quality can be used to determine the effect of each variable on consumer decisions. the author uses a quantitative writing method with a descriptive approach to describe how the Brand Image variable, Service Quality variable, and Price variable simultaneously and partially influence the customer's decision to use Nail Studio services. the population in this study were all consumers who use beauty services, in this case nail art at Luna Bee Nail Studio and Hello Gorgeous Manado. This study collected as many as 100 respondents for data processing. Based on the results of data processing, several conclusions were the brand image variable (X1) used in this study partially has a positive and significant effect on Purchase Decision (Y) at Luna Bee and Hello Gorgeous Nail Art Manado. The Service Quality variable (X2) used in this study partially has no effect on Purchase Decision (Y) at Luna Bee and Hello Gorgeous Nail Art Manado. The variable Price (X3) used in this study partially has a positive and significant effect on Purchase Decision (Y) at Luna Bee and Hello Gorgeous Nail Art Manado.